IMPLEMENTASI STRATEGI HABITUASI DALAM MEMBENTUK AKHLAK TERPUJI SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MADRASAH IBTIDAIYAH MIFTAHUS SUDUR KARANG PELAN OMBEN SAMPANG - Moh. Fathur Rohman; Abdul Munib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the habituation strategy of reading short surahs before learning in forming students' commendable morals in the subject of Akidah Akhlak at Madrasah Ibtidaiyah Miftahus Sudur Karang Pelan Omben Sampang, and to identify supporting and inhibiting factors in its implementation. This study uses a qualitative approach with a descriptive type. Data collection techniques include participatory observation, in-depth interviews, and documentation studies. Data analysis uses the interactive model of Miles, Huberman, and Saldaña which consists of data condensation, data presentation, and drawing conclusions. The results of the study indicate that: (1) the implementation of the habituation strategy is carried out through routine reading of short surahs of juz 'Amma for 10-15 minutes before the Akidah Akhlak learning begins, with structured planning, implementation, and evaluation stages; (2) supporting factors include teacher commitment, support from the head of the madrasah, the religious culture of the madrasah, and student enthusiasm, while inhibiting factors include limited time, differences in students' reading abilities, and the influence of the environment outside the madrasah; (3) The impact of habituation is seen in increased student discipline, honesty, politeness, and responsibility. This study recommends strengthening the habituation program through a more systematic integration of short surah recitation with the Aqidah and Ethics material.